PENGARUH WORK-LIFE BALANCE DAN KOMITMEN AFEKTIF TERHADAP KEPUASAN KARIR PADA PT. SINAR KARYA DUTA ABADI - ANDINI, INTAN (Jurnal Ilmu Manajemen (JIM), 2017)
This study aims to examine and analyze the effect of work-life balance and affective commitment to career satisfaction at PT. Sinar Karya Duta Abadi. Data obtained from the results of questionnaires and interviews. Samples in this study were 35 respondents taken with saturated sample method. Technique of collecting data used is questionnaire technique which disseminated directly to the respondent in this case is permanent employee of nonshift at Department of Maintenance PT. Sinar Karya Duta Abadi. Data analysis techniques using PLS (Partial Least Square). In addition, this study uses Likert scale as a measurement scale.The results of this study indicate work-life balance and affective commitment affecting career satisfaction. Keywords : Work-Life Balance, Affective Commitment, Career Satisfaction